ASSESSING DRUGS ABUSE AWARENESS OF MEDICAL STUDENTS IN BAGHDAD (Modern American Journal of Medical and Health Sciences, 2026)
In the current study, (148) students from the college of health and medical technology-Middle technical university, Baghdad were enrolled during the period from October 2024 to January 2025. A structured questionnaire form was completed by the students for assessing their knowledge and attitude toward drug abuse. The results showed that (47.3%) of the study group were in the age group (20–24) years, (41.9%) in the age group (25–29) years, (9.5%) in the age group (30–39) years and (1.4%) in the age group (>40) years,. All the participants (100%) had heard of drug abuse, (74.3%) defined it as: inconsistent use of drugs, and (95.9%) recognized it as harmful to health. The most frequently identified signs were poor self-control (54.7%) and, unexpectedly, increased work interest (35.8%), reflecting some misconceptions. Economic effects were cited by (35.8%), social by (29.7%), psychological by (29.1%), and physical effects by only (5.4%). For drug prevention, (58.1%) favored peer-to-peer programs and (29.7%) counseling. For treatment, (41.2%) endorsed providing a calm environment and (38.5%). The overall drug abuse awareness was high among medical and health students, misconception in regard to its effect and symptom persistence. For strengthening students competency to address drug abuse, it is recommended to hold targeted educational intervention, particularly within departments having lesser knowledges, and reinforcements of accurate treatment and prevention strategy.